ROAD GEOMETRIC PLANNING USING AUTOCAD® CIVIL 3D: A CASE STUDY OF LEUWIKIDANG HIGHWAY, MAJALENGKA - Fahmi Nabhan Luthfiansyah; Amanatullah; Adinda Fajarika (LEADER: Civil Engineering and Architecture Journal, 2024)
Jalan Raya Leuwikidang is a land transportation infrastructure that plays an important role in the field of transportation, especially in the distribution of goods and services. The road has horizontal and vertical alignment and is slightly less safe for road users. This study aims to review the horizontal and vertical alignment analysis and compare the results of the review with the planning results based on road convenience. This research method uses quantitative methods. The data used in this study are the results of a review of horizontal alignment, vertical alignment, superelevation, jph and jpm.